2016
DOI: 10.1111/trf.13755
|View full text |Cite
|
Sign up to set email alerts
|

The confusion continues: results from an American Association for the Surgery of Trauma survey on massive transfusion practices among United States trauma centers

Abstract: BACKGROUND:Massive transfusion practices have undergone several recent developments. We sought to examine institutional practices guiding hemostatic resuscitation in the setting of massive hemorrhage. STUDY DESIGN AND METHODS:A 37-question online survey was sent to American Association for the Surgery of Trauma members. RESULTS:A total of 191 surgeons from 125 institutions completed the survey. Level I and II centers composed 70 and 18% of responding sites, respectively. A total of 123 institutions have a mass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(48 citation statements)
references
References 34 publications
0
47
0
1
Order By: Relevance
“…Ultimately a simple user-friendly trigger for activation of a massive transfusion protocol is in need for trauma centers in the United States. In a recent survey evaluating blood product utilization in 125 level I and II trauma centers in 2016, 98% reported having a massive transfusion protocol, yet only 7% used a validated scoring mechanism to activate the protocol (38). …”
Section: Discussionmentioning
confidence: 99%
“…Ultimately a simple user-friendly trigger for activation of a massive transfusion protocol is in need for trauma centers in the United States. In a recent survey evaluating blood product utilization in 125 level I and II trauma centers in 2016, 98% reported having a massive transfusion protocol, yet only 7% used a validated scoring mechanism to activate the protocol (38). …”
Section: Discussionmentioning
confidence: 99%
“…Despite this, uptake into routine clinical practice has been slow. An audit from adult practice revealed only 9–18% of sites routinely incorporated VHA into their MHP . A similar audit of paediatric practice revealed that in the institutions that had access to VHA they were used to guide management in less than 50% of cases .…”
Section: Methodsmentioning
confidence: 99%
“…An audit from adult practice revealed only 9-18% of sites routinely incorporated VHA into their MHP. 24 A similar audit of paediatric practice revealed that in the institutions that had access to VHA they were used to guide management in less than 50% of cases. 25 Part of the reason for slower integration is the concern around validation of VHA use in paediatric trauma management, and clinician familiarity and confidence with their interpretation.…”
Section: Vha and Major Haemorrhage Protocolsmentioning
confidence: 99%
“…Beyond the initial assessment of the patient, transfusion strategies can differ widely. Most hospitals have adopted massivetransfusion(MTP) protocols (48,49), but variation remains between the ratios of RBCs to FFP administered.…”
Section: Emergency Departmentmentioning
confidence: 99%